2020
DOI: 10.2478/jtim-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early cytokine storm in patients with septic shock after abdominal surgery

Abstract: Objectives: To explore the characteristics of cytokine storm in patients with septic shock after abdominal surgery, examine its relationship with clinical data, and determine intervention timings.Materials and Methods: We prospectively observed a cohort of patients with abdominal infection admitted to the surgical intensive care unit (ICU) after surgery (shock group). A control group of healthy individuals was used for comparison. Plasma samples and clinical data recorded at 0, 12, 24, 48, and 72 h after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…An excessive proinflammatory response and/or exaggerated anti-inflammatory response further induce cellular dysfunction and death, ultimately resulting in multiorgan dysfunction syndrome and death ( 36 ). Similar to other studies ( 37 , 38 ), we also found that serum levels of the proinflammatory cytokines IL-1β and TNF-α were significantly elevated in septic mice ( Fig. 2G and H ).…”
Section: Discussionsupporting
confidence: 91%
“…An excessive proinflammatory response and/or exaggerated anti-inflammatory response further induce cellular dysfunction and death, ultimately resulting in multiorgan dysfunction syndrome and death ( 36 ). Similar to other studies ( 37 , 38 ), we also found that serum levels of the proinflammatory cytokines IL-1β and TNF-α were significantly elevated in septic mice ( Fig. 2G and H ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the serum resistin levels correlated with systemic inflammation, as indicated by the serum TNF-α level, in patients. TNF-α is an important pro-inflammatory cytokine ( 60 ). The elevated expression of TNF-α in muscle or circulatory system is associated with loss of muscle strength and muscle mass ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…An unnecessary surgery in such patients can lead to a cytokine storm and deterioration of patients’ condition. 12 Therefore, a decision for surgical approach should be taken with much caution and conservative treatment might be considered on admission. A multidisciplinary decision is necessary, and laboratory and imaging findings would help for a proper diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%